The Practical Philosophy of AI-Assistants : An Engineering-Humanities Conversation - Gupta, Suman, 1966-; Tu, Peter H. (New Jersey ; London : World Scientific, 2024)
"The Practical Philosophy of AI-Assistants presents a formal conversation between an AI engineer, Peter, and a humanities researcher, Suman. It is written so that specialist terms and concepts in AI research are accessible to a humanities researcher and humanities theories are easily grasped by an AI engineer. The argument concerns setting up ground rules to design an AI-Assistant, i.e. an AI system that could act as a personal friend, consultant and confidante for every individual and be integrated into our everyday life. These rules apply to four large areas of AI development: recognition and identification, communication, explanation, and civility. In discussing these areas, this book also gives an accessible account of the current state of AI research, as well as adding nuance to the underpinning assumptions of relevant technologies and reflecting on their social implications. The broader ideological objective of The Practical Philosophy of AI-Assistants is captured by the phrase 'practical philosophy', which expresses a commitment to bringing AI development to work towards a good life for all"--
t Facing up to challenges / Peter Tu t Elephants and monkeys / Suman Gupta -- t Alan Turing, Kurt Gödel, and David Hilbert go to a bar... / Peter Tu -- t The Tomasello assumption and virtuous cooperation / Suman Gupta -- t t t t Decisions and choices / Suman Gupta.
Includes index
Includes bibliographical: pages 247-255
Keywords: Intelligent personal assistants (Computer software); Artificial intelligence -- Social aspects